Concurrency Control in Distributed Databases - Sahab, Zoia (Journal of Natural Sciences – Kabul University, 2020)
Database systems play a critical role in modern society, being used by various organizations such as banks, hospitals, airlines, and internet search engines, all of which involve multiple users or computers accessing a database. Advances in technology have led to the development of large databases that store various types of data. To manage this data, new and innovative systems, such as distributed databases, have been introduced. With the use of these systems, concurrency control of transactions becomes a major concern. This research first discusses distributed database systems and then describes the algorithms used to resolve concurrency issues. After comparing these algorithms, the study concludes that ACID properties are essential for controlling transactions in databases and must be maintained.